SEX REVERSAL IN SIAMESE FIGHTING FISH LARVAE BY THERMAL MANAGEMENT - Igor de Fiuza FRANÇA; Guilherme Melgaço HELUY; Érica Beatriz SCHULTZ; Wilson de Oliveira VIANNA; Marcelo Maia PEREIRA; Leonardo Rocha Vidal RAMOS (Boletim do Instituto de Pesca)
The present study evaluated the influence of thermal management during the larviculture of Betta splendens on survival and sex ratio, aiming to increase the proportion of males. Newly hatched larvae were subjected to different thermal regimes, namely, T25, T28, T30 and T33 (25, 28, 30 and 33ÂºC, respectively). The experiment was laid out in a completely randomized design, with 4 treatments and 10 repetitions. Thermal treatment was maintained until 15 days post-hatch (DPH). Mortality was determined at the end of the thermal regime and again at 45 DPH. At the end of the experiment, the number of males and females obtained in the different thermal treatments was counted to analyze the obtained sex ratio. There was a significant effect on mortality as a function of temperature only at 15 DPH (p <0.001), with the lowest values recorded in treatments T25, T28 and T30. In terms of sex ratio, up to 65% of males were obtained in treatment T33 (p = 0.037). In conclusion, thermal management during the larval period can be a strategy to increase the proportion of males, but the increase in mortality due to the rise in temperature should be considered.